2020
DOI: 10.1038/s41598-020-72262-6
|View full text |Cite
|
Sign up to set email alerts
|

The distinctive geographic patterns of common pigmentation variants at the OCA2 gene

Abstract: Oculocutaneous Albinism type 2 (OCA2) is a gene of great interest because of genetic variation affecting normal pigmentation variation in humans. The diverse geographic patterns for variant frequencies at OCA2 have been evident but have not been systematically investigated, especially outside of Europe. Here we examine population genetic variation in and near the OCA2 gene from a worldwide perspective. The very different patterns of genetic variation found across world regions suggest strong selection effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Currently, it includes two SNPs in the OCA2/HERC2 region (rs12913832 and rs1800407). The rs1800407 SNP is a missense SNP in OCA2, known to be involved in pigmentation variation ( Donnelly et al., 2012 ; Pospiech et al., 2014 ; Kidd et al., 2020 ). This SNP did not pass the quality control in our study, but other SNPs in high LD are not within the fine-mapped 95% credible sets.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, it includes two SNPs in the OCA2/HERC2 region (rs12913832 and rs1800407). The rs1800407 SNP is a missense SNP in OCA2, known to be involved in pigmentation variation ( Donnelly et al., 2012 ; Pospiech et al., 2014 ; Kidd et al., 2020 ). This SNP did not pass the quality control in our study, but other SNPs in high LD are not within the fine-mapped 95% credible sets.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Saudi population (1) observed the SNP rs1800407 was not polymorphic in the Saudi population with the presence of the allele G. In this study, concluded the rs1800407 indicating of eye color with the rs12913832 because of the linkage disequilibrium coefficient between alleles of these SNPs strong associated with eye color. Irises exhibit extensive variation across Europe and a small degree of pigmentation from blue to green and brown in North Africa, Middle East, and Asia (8).…”
Section: Genotyping Of Herc2 (Rs12913832) and Oca2 (Rs1800407) Genesmentioning
confidence: 99%
“…particularly strong signal is found in a region containing the OCA2 and HERC2 genes with a -log10 P > 230. Both OCA2 and HERC2 are well known genes involved in pigmentation in both humans and mice and have been shown to be involved in iris, skin and hair pigmentation in human (66)(67)(68)(69). Pathogenic variation in OCA2 including CNVs are known to be a leading cause of the rare genetic disorder oculocutaneous albinism and an increased susceptibility to melanoma (70)(71)(72).…”
Section: Copy Number Variation Associations Testing In the Uk Biobankmentioning
confidence: 99%
“…For example, for hair colour (Figure 2A) after fine mapping we detect 30 copy number variable regions that pass genome wide significance, the majority of which (20/30) have been found to be associated with pigmentation by previous SNP GWAS (Supplementary particularly strong signal is found in a region containing the OCA2 and HERC2 genes with a -log10 P > 230. Both OCA2 and HERC2 are well known genes involved in pigmentation in both humans and mice and have been shown to be involved in iris, skin and hair pigmentation in human (66)(67)(68)(69). Pathogenic variation in OCA2 including CNVs are known to be a leading cause of the rare genetic disorder oculocutaneous albinism and an increased susceptibility to melanoma (70)(71)(72).…”
Section: Copy Number Variation Associations Testing In the Uk Biobankmentioning
confidence: 99%